Ramy prawne raportowania ESG w Unii Europejskiej – ewolucja od NFRD do CSRD - Kostecka-Jurczyk, Daria; Marak, Katarzyna (PRAWO i WIĘŹ, 2025)
The transition to a zero-emission economy and sustainable development requires us to reduce our use of fossil fuels and implement legal and reporting mechanisms that oblige businesses to comply with environmental and social standards. One of the key challenges has become the reporting of non-financial information, including environmental, social and corporate governance (ESG) aspects. Initially, this data was reported in accordance with the 2014 NFRD Directive, which was replaced in 2024 by the CSRD Directive, and further legislative changes regarding non-financial reporting are currently being implemented and planned. This paper presents the evolution of the legal framework for ESG reporting in the European Union, identify differences in reporting obligations under the aforementioned directives; it also highlights problems related to the lack of consistent, uniform, and mandatory ESG reporting standards. Despite the implementation of the CSRD Directive, the paper emphasises that companies still have too much discretion in selecting the information to be reported, which hinders comparability and verification. The analysis confirms that the abundance of data and the qualitative nature of ESG indicators increase interpretative risks and may undermine the objectives of non-financial reporting.